Sintesis dan Karakterisasi Senyawa Kompleks [Cu(H2O)2(NH3)4]SO4 - Rebecca Febi Permata Br Simorangkir; Amita M. Siregar; Putri Soviana Pakpahan; Yusi Yulfani Siagian; Iis Siti Jahro (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to synthesize and characterize the complex compound [Cu(H2O)2(NH3)4]SO4 through ligand substitution reaction between CuSO4·5H2O and ammonia solution in the context of coordination chemistry learning. The research problem is focused on the mechanism of complex formation, color changes as an indicator of the formation of coordination compounds, synthesis efficiency based on yield values, and confirmation of the presence of complex constituent ions. Laboratory experimental methods were carried out through complex formation, crystallization, separation, and drying of crystals, as well as classical characterization using solubility tests and chemical reactions with HCl, NaOH, and BaCl₂. The results showed a change in the color of the solution from light blue to deep dark blue which indicates the formation of the complex [Cu(H₂O)₂(NH₃)₄]²⁺ due to the substitution of water ligands by ammonia. Dark blue crystals were successfully obtained with a yield of 91.46% which indicates high synthesis efficiency. Characterization tests confirmed the presence of NH₃ ligands, Cu²⁺ ions, and SO₄²⁻ ions as constituents of the complex. These findings are consistent with valence bond theory and crystal field theory in explaining changes in the coordination structure and optical properties of the complex, making this procedure a potential alternative for simple laboratory experiments in coordination chemistry.